Strength and durability properties of concrete made with recycled coarse aggregate and seashore sand - D. Kalaimani; G. Srinivasan (Universitas Mercu Buana, 2024)
The process of depletion of sources of natural aggregates poses challenges to produce technically and environmentally suitable concrete. Aggregate compositions found in construction and demolition (C&D) waste offer potential alternatives to natural coarse aggregates. Additionally, the utilization of abundantly available natural material like seashore sand, as a replacement for river sand, can present a viable solution to this problem. This research paper investigates the performance of concrete that incorporates 40% recycled coarse aggregates, along with varying percentages of seashore sand as replacements for river sand (0%, 10%, 20%, 30%, 40%, 50%, and 100%). The evaluation focuses on strength properties, including compressive strength tests on cylinders and impact resistance tests, as well as durability properties such as water penetration tests under pressure and sulphate attack tests. The experimental results indicate that concrete incorporating both recycled coarse aggregates and seashore sand replacements yields favorable outcomes in terms of strength and durability when compared to the controlled concrete, particularly at suitable replacement proportions.